2017
DOI: 10.1002/bdm.2035
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Scoping Review of the Choice Architecture Movement: Toward Understanding When and Why Nudges Work

Abstract: In this paper, we provide a domain-general scoping review of the nudge movement by reviewing 422 choice architecture interventions in 156 empirical studies. We report the distribution of the studies across countries, years, domains, subdomains of applicability, intervention types, and the moderators associated with each intervention category to review the current state of the nudge movement. Furthermore, we highlight certain characteristics of the studies and experimental and reporting practices that can hinde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
187
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(190 citation statements)
references
References 53 publications
2
187
0
1
Order By: Relevance
“…In our review, we used terms for choice architecture techniques as they are commonly used in the choice architecture literature (e.g. 'default change' and 'anchoring'), because those terms refer to more specific techniques than the techniques from the taxonomy from Michie et al [10,12]. In addition to choice architecture techniques, a wide variety of other BCTs exists [131], such as social support or punishment, but our review did not look at combinations of choice architecture and such other BCTs.…”
Section: Summary Of Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…In our review, we used terms for choice architecture techniques as they are commonly used in the choice architecture literature (e.g. 'default change' and 'anchoring'), because those terms refer to more specific techniques than the techniques from the taxonomy from Michie et al [10,12]. In addition to choice architecture techniques, a wide variety of other BCTs exists [131], such as social support or punishment, but our review did not look at combinations of choice architecture and such other BCTs.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…A promising approach to break individuals' unhealthy habits and promote healthy behavior (e.g. increase physical activity and decrease sedentary behavior) is to make subtle changes to the micro-environment in which individuals make decisions, an approach termed 'choice architecture' or 'nudging' [8][9][10][11][12]. The micro-environment refers to relatively small settings, such as homes and workplaces [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other studies find individual response to specific interventions to depend on several factors, such as preference strength, socio-demographic characteristics, and the current mental and visceral states. Understanding the interplay of these factors with the choice architecture is crucial to create adequately targeted interventions (see Szaszi et al 2018 for a recent review). For instance, interventions based on health priming theoretically rely on (or should be at least amplified by) an existing goal to eat healthier, and the individual needs to know that product A is more in line with achieving this health goal than product B.…”
Section: Effective Behavioural Policymentioning
confidence: 99%
“…Part of the challenge in identifying the limits of nudging is the lack of information on unsuccessful interventions. A recent systematic review of nudge studies found that just 18% of interventions reported in a set of 116 studies were unsuccessful 5 . The problem is that it's uncertain what this finding means for the state of our knowledge.…”
mentioning
confidence: 99%